Trends in Project Based Learning (PjBL) Models for Developing Creative Thinking Skills in Science Learning: A Bibliometric Review (2019–2024) - Maria Rosalinda Febrianti Sawu (International Journal of Science Education and Science, 2026)
Education in the 21st century, students need to be equipped with life skills, one of which is creative thinking skills, which are important to face global challenges and rapid technological developments. This study aims to review research trends related to the Project Based Learning (PjBL) model to improve students' creative thinking skills in science learning in the period 2019 to 2024. The method used in this research is descriptive and analytical, with data obtained from scientific publications indexed by Google Scholar, using tools such as Publish or Perish and Dimension.ai. The analysis process was carried out using PRISMA guidelines to filter and assess the quality of documents. Data analysis was conducted through bibliometric analysis with the help of VOSviewer software to map the main keywords. The results showed that the trend of research on PjBL for creative thinking skills continued to increase significantly from 2019 to 2024, but decreased in 2024. Scientific articles are the dominant form of publication, stating that the PjBL model is one of the models that is widely recognized as effective for improving creative thinking skills. Some of the keywords that often appear are “creative thinking skills, critical thinking, PjBL, PBL, motivation, and STEM Project”. This research provides a comprehensive view of the development of the PjBL trend in science learning and provides an overview of the use of PjBL in science learning